Otonomi Daerah: Dakwah Politik Abbasiyah - Azizah Fitrah (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2004)
At -early Daulah Abbasiyah, governance patern character govemance of Abbãsiyah happened dissolution whicn is autonomous that dynasties. Each small dynasty under authority of pertinent province governor. Its relation with khilafah is marked by givingpayment of tribute. This article tries to analyze that situation with the concept of districs